2015
DOI: 10.1177/0300060515574922
|View full text |Cite
|
Sign up to set email alerts
|

Conclusiveness of the Cochrane reviews in gynaecological cancer: A systematic analysis

Abstract: Objective: To assess the conclusiveness of Cochrane reviews in the field of gynaecological cancer. Methods: The Cochrane Library was searched for reviews regarding gynaecological cancer published between 1 January 2000 and 1 November 2014. Data were extracted from each paper and the conclusiveness of each review was assessed. Results: The study included 66 reviews, 41 (62.1%) of which were conclusive. Of these, 58 included randomized controlled trials (RCTs), 37 (63.8%) of which were conclusive. Conclusive rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Furthermore, this study demonstrated that the number of participating patients and RCTs affects the ability of a CR to conclude. This result was consistent with that of previous studies (2) , (3) , (4) , (5) , (6) , (7) . However, the number of included RCTs was generally small―approximately 7.6 and 1.7 RCTs were included in the conclusive and inconclusive studies, respectively.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Furthermore, this study demonstrated that the number of participating patients and RCTs affects the ability of a CR to conclude. This result was consistent with that of previous studies (2) , (3) , (4) , (5) , (6) , (7) . However, the number of included RCTs was generally small―approximately 7.6 and 1.7 RCTs were included in the conclusive and inconclusive studies, respectively.…”
Section: Discussionsupporting
confidence: 94%
“…Conversely, inconclusiveness is characterized by insufficient data (2) . According to previous studies, 45%-80% of CRs are conclusive (2) , (3) , (4) , (5) , (6) , (7) . However, even when conclusiveness is achieved, additional high-quality research is often required.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…An even lower proportion of Cochrane reviews with high-quality evidence was identified in the field of orthodontics (2%). 5 Findings from previous analyses of Cochrane reviews in other medical specialties have varied, with some reporting a large proportion of conclusive reviews, 6 , 7 whereas others were more likely to be inconclusive. 8 , 9 The total number of studies and total number of included participants were associated with review conclusiveness.…”
Section: Discussionmentioning
confidence: 99%